Parallel Study of Medodhara Kala and Abdominal Adipose Tissue with Special Reference to Sthoulya (Obesity) (International Journal of Ayurveda and Pharma Research, 2023)
Obesity which is neuroendocrine disorder seems to be common predisposing factor for almost all non-communicable diseases. This neuroendocrine disturbance causes multiple systemic disorders and finally Ayurhasa (reduction in longevity of life) by various means. Ayurveda mentioned eight pathophysiological conditions considered as Nindya (worse conditions). Atisthool (excessive weight) is one of these conditions due to improper Aahara (dietary habits), Vihar (sedentary life style) and changed sleep pattern. Apachita meda (improperly metabolized fat) deposited in Udara (abdomen). Medodharakala according to Ayurveda and abdominal linings bear several similar characteristics related to fat and Medodhatu deposition. Deterioration of functioning of Medodhara kala leads to deposition of Apachita meda leading to Sthoulya. In obesity, abdominal wall, space between organs stores much amount of adipose tissue (site of Meda deposition). So this article reveals with parallel study of Medodhara kala and abdominal adipose tissue to find out similarity.